PENGUATAN LITERASI SAINS DAN PENDAMPINGAN PEMBUATAN MODUL AJAR UNTUK GURU SD - Limiansih, Kintan; Dewi, Agata Mustika Kusuma (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2023)
The challenge most often faced today is how to make students and teachers aware of the importance of literacy. One of the important literacy is scientific literacy. Scientific literacy is defined as a person's ability to use scientific knowledge and scientific process skills to understand and make decisions about the natural environment. In this community service, strengthening scientific literacy and assisting in the manufacture of teaching modules for elementary school teachers at Kanisius Demangan Baru Elementary School. The implementation of community service is carried out in 3 stages, namely: (1) mapping the teacher's interest in scientific literacy (2) the team prepares training materials based on the mapping (3) strengthening scientific literacy and assisting in making teaching modules. From this community service, teachers can create teaching modules that can train students' scientific literacy skills well.